Fluid dynamic characterisation of porous solids in catalytic fixed-bed reactors - Horneber, Tobias; Rauh, Cornelia; Delgado, Antonio (Microporous and Mesoporous Materials, 2012)
3D numerical simulations of structured open-cell foams, more precisely the tetrakaidecahedron geometry (Kelvin cell geometry) are presented. The velocity and pressure field for a single cell with varied surface roughness and the whole reactor with the same pore size are calculated in order to show the influence of the surface roughness regarding the pressure drop and the influence of the length of the whole reactor regarding the velocity development, respectively. The numerical results are compared using dimensionless numbers such as Reynolds number, Euler number and friction factor. © 2011 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2012.tech.ITC.stmmec.fluidd
Keywords: CFD of metal foam; Kelvin cell geometry; Numerical simulations; Pressure drop; Surface roughness

Numerical simulations of fluid dynamics in carrier structures for catalysis: characterization and need for optimization - Horneber, Tobias; Rauh, Cornelia; Delgado, Antonio (Chemical Engineering Science, 2014)
3D fluid dynamic numerical simulations of different structured open-cell foams are presented: a cubic lattice, the tetrakaidecahedron geometry (Kelvin cell geometry), and the diamond structure. The simulations are done with the open-source software OpenFOAM. Beneath the pressure drops of the different structures, which are compared using dimensionless numbers such as Reynolds number and Euler number, also the development of velocity and its frequency distribution, as an important parameter for chemical reactions, are evaluated. As a main result, the diamond structure provides good conditions with respect to dwell time distributions for the underlying chemical reaction. All the results give a deep knowledge in terms of the underlying principles and optimization approaches. © 2014 Elsevier Ltd.
UnivIS-Import:2015-03-09:Pub.2014.tech.ITC.stmmec.numeri_7
Keywords: Catalyst support; Computational fluid mechanics; Metal foam; Porous media; Pressure drop; Tetrakaidecahedron structure

Numerische Simulation von Trägerstrukturen in der Katalyse - Horneber, Tobias; Rauh, Cornelia; Delgado, Antonio (Chemie Ingenieur Technik, 2012)
Keywords: Trägerstrukturen; Katalyse